Scalable synthesis and structural characterization of reversible KLK6 inhibitors. Issue 41 (21st September 2022) - Baumann, Andreas; Isak, Daniel; Lohbeck, Jasmin; Jagtap, Pravin Kumar Ankush; Hennig, Janosch; Miller, Aubry K.
Abstract : We report scalable syntheses of two potent and selective kallikrein related peptidase 6 (KLK6) inhibitors, as well as X-ray crystal structures of both inhibitors as protein-ligand complexes. Abstract : Scalable asymmetric syntheses of two kallikrein-related protease 6 (KLK6) inhibitors are reported. The inhibitors are assembled by linking enantiomerically enriched fragments via amide bond formation, followed by conversion of a cyano group to an amidine. One fragment, an amine, was prepared using the Ellman auxiliary, and a lack of clarity in the literature regarding the stereochemical outcome of this reaction was solved via X-ray crystallographic analysis of two derivatives. Complexes of the inhibitors bound to human KLK6 were solved by X-ray crystallography, revealing the binding poses.